ANALISIS MOTIVASI BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 1 RAMBAH HILIR - Hazarida, Rita; Deswita, Hera; Richardo, Rino (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2015)
The purpose of this study research was to describtion of learning motivation studentsâ Mathematic at class VIII SMP Negeri 1 Rambah Hilir. The design of this research was descriptive qualitative research. The total number of this subjects were 21 students. It was consist of 9 students ware in hight motivation, 4 students were in average motivation and 8 students were in low . To select the subject it used by purposive sampling. the data was collected by using questionere and interview. the technique of analyze the data was using (1) reduction of the data, (2) presentation of the data, (3) conlution the motivation of students learning. matematic, and then the risearcher used triangulation technique in validity of the data. Based on the research was done, it was found that there were two difference was significant it can be found in indicator: (1) were the studentsâ (2) used chance in time of lesson